2021
DOI: 10.24071/ijiet.v5i2.3461
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Gamification Concept Inside Online Classroom Activities to Promote Students’ Engagement

Abstract: Online learning has made massive development nowadays. Due to the spread of Covid-19, the government made a policy to prohibit physical meetings in schools. However, this new policy caused a problem of engagement in online learning. During the lesson, students are giving slow and minimum responses to the teacher’s instruction. This happens in most of the school that operates online learning. Therefore, a solution to improve engagement in online classroom is needed. The implementation of the gamification concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Numerous researchers concluded plethora benefits from the gamification method in learning where students' motivation has been increased both intrinsically and extrinsically over the course of time, sustainable engagement throughout the learning process, and better academic achievements (Papp, 2017;Rahman, Panessai, Noor, & Salleh, 2018;Sulispera & Recard, 2020;Jonathan & Recard, 2021). Al-Azawi, Al-Faliti, & Al-Blushi (2016) found the students regardless of their backgrounds [e.g., gender, ethnicity, high or low achievers] have increased learning engagement due to the immediate feedback and reward, cultivate self-driven learning where the students independently set their milestones which in particular maintain positive learning attitude, and pose students with challenges that enhance curiosity in learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous researchers concluded plethora benefits from the gamification method in learning where students' motivation has been increased both intrinsically and extrinsically over the course of time, sustainable engagement throughout the learning process, and better academic achievements (Papp, 2017;Rahman, Panessai, Noor, & Salleh, 2018;Sulispera & Recard, 2020;Jonathan & Recard, 2021). Al-Azawi, Al-Faliti, & Al-Blushi (2016) found the students regardless of their backgrounds [e.g., gender, ethnicity, high or low achievers] have increased learning engagement due to the immediate feedback and reward, cultivate self-driven learning where the students independently set their milestones which in particular maintain positive learning attitude, and pose students with challenges that enhance curiosity in learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dengan meningkatkan motivasi, keterlibatan, kemampuan kognitif, dan interaksi antar siswa, gamifikasi membantu menciptakan lingkungan pembelajaran yang menyenangkan dan efektif dalam mengembangkan kemampuan bahasa siswa (Mailis, 2022). Berdasarkan hasil penelitian yang dilakukan oleh Smiderle et al (2020), Krisbiantoro (2020), dan (Jonathan & Recard, 2021) menunjukkan bahwa gamifikasi pendidikan dapat meningkatkan tingkat keterlibatan siswa seperti halnya yang dapat dilakukan oleh permainan, untuk meningkatkan keterampilan mereka dan mengoptimalkan pembelajaran.…”
Section: Gamification In Educationunclassified
“…It can be defined as how much time, commitment, and effort are devoted to the learning process (Kahn et al, 2017;Khaleel et al, 2020;Ma et al, 2015). Miller in Jonathan and Recard (2021) state that engagement is the students' willingness to actively participate in the learning process, as well as demonstrating sustained involvement and a positive emotional tone toward learning experiences. Behavioral engagement includes students' active participation in the learning process, such as accessing the material, doing assignments, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement is positively correlated with motivation, i.e., higher motivation tends to lead to higher engagement and vice versa (Yu & Gao, 2020). Numerous studies have reported the essential role of game-based learning in engaging learners (Inayati & Waloyo, 2022;Jonathan & Recard, 2021;Nikmah, 2020;Nuci et al, 2021). Jonathan and Recard (2021) mention that there are at least three reasons why gamification is effective in improving learning engagement.…”
Section: Introductionmentioning
confidence: 99%